Investigations on Biomimetic PLA Scaffold Fabricated by Fused Deposition Modelling - Singh, Daljeet (My University, 2018)
Now-a-days polylactic acid (PLA) is widely used in orthopedics surgeries as implants material due to well mechanical characterization and biomedical properties. But the polylactic acid implants suffer from slow degradation rate when it used in real life example. In this research, fabricate the PLA specimens using additive manufacturing technique and assess the mechanical characterization and degradation behavior of polylactic acid with different parameters. The three different process parameters (infill percentage, layer thickness and infill pattern) set on three levels for fabricating the various specimens. Simulated body fluid (SBF) used for in vitro study of the experiment. Immersed specimens in simulated body fluid for 7,14 and 28 days. To check the mechanical characterization of these samples on Universal Testing Machine before and after immersion in SBF solution. The amount of apatite formation on the surface of different parts show the biological behavior of different process parameters. The infilling percentage and infilling patterns greatly affect the formation on the surface of workpiece due to their high surface area to volume ratio. High infill percentage results the maximum mechanical strength and low degradation rate. On the other hands, the workpiece with low infill percentage results gives the minimum mechanical strength and higher degradation rate. The apatite formation is also high in case of low infill percentage. The study concludes the positive effect of process parameters on degradation rate and biocompatible behavior of polylactic acid implants.
Keywords: Polylactic acid; Additive manufacturing; Simulated body fluid; Degradation